The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3846/16486897.2015.1068781
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metals Using Bacterial Bio-Flocculants of Bacillus Sp. And Pseudomonas Sp.

Abstract: Abstract. Trinitrotoluene (TNT), a commonly used explosive for military and industrial applications, can cause serious environmental pollution. 28-day laboratory pot experiment was carried out applying bioaugmentation using laboratory selected bacterial strains as inoculum, biostimulation with molasses and cabbage leaf extract, and phytoremediation using rye and blue fenugreek to study the effect of these treatments on TNT removal and changes in soil microbial community responsible for contaminant degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Pseudomonas sp. showed a 97.9% Pb, 93.5% Cd, and 68% Cu removal efficiency from contaminated industrial wastewater is reported [ 72 ]. Surface binding/reduced uptake, increased efflux intracellular sequestration, enzyme detoxication, and active transport are among the proven mechanisms of tolerance [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas sp. showed a 97.9% Pb, 93.5% Cd, and 68% Cu removal efficiency from contaminated industrial wastewater is reported [ 72 ]. Surface binding/reduced uptake, increased efflux intracellular sequestration, enzyme detoxication, and active transport are among the proven mechanisms of tolerance [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is valid in light of the results obtained in this study and similar results reported elsewhere, were Pseudomonas sp. showed a 97.9% lead (Pb), 93.5% cadmium (Cd) and 68% cupper (Cu) removal efficiency from contaminated industrial wastewater [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, bacillus flocculant has a good treatment effect on Cu 2+ and Pb 2+ . The removal rate of Cd 2+ by Pseudomonas can reach 93.5% [68]. The results show that the biosorption ability of the exopolysaccharides is much higher than that of the extracellular proteins in the extracellular polymers.…”
Section: Heavy Metal Wastewater Treatmentmentioning
confidence: 90%